BATIMETRY MAPPING AND BASIC SEDIMENT TYPES IN SASAK BEACH WATERWEST PASAMAN DISTRICT WEST SUMATERA PROVINCE - Imron Imron; Rifardi Rifardi; Joko Samiaji (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractBathymetry is a measure of high and low seabed where bathymetry maps provide information about the seabed.This research was conducted in November 2018 - January 2019,in the waters of the Sasak coast of West Pasaman district. This study aims to determine the depth and shape of the seabed morphology as well as the type of sediment,The research method used is a survey method, then the sampling point is determined by purposive sampling,the fixing fixation point consists of 100 points and 9 sediment sampling points.Then sediment analysis and bathymetry data processing are performed. The results showed the depth of water in the study area between 4 to 14.5 meters and has a type of seabed morphology that is classified as gentle.The distribution of basic sediments in the study area consists of three (3) types of sediment fractions, namely gravel, sand and mud,The type of sediment at each sampling point is based on the proportion of gravel particle content,sand and mud are classified according to Shepard's triangle, weight percentage fraction and sediment type at each station point.Keywords :Bathymetry, Sediment.